2000
DOI: 10.1097/00006842-200007000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Immune, Endocrine, and Psychological Responses in Civilians Displaced by War

Abstract: Chronic psychological stress elicited multiple, predominantly stimulatory influences on immune functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
1
24
1
1
Order By: Relevance
“…Tucker et al (2004) found higher levels of IL-1 and lower levels of IL2-receptor in PTSD subjects compared to traumatized controls, although a potential limitation of this study was that they included several PTSD subjects with inflammatory conditions warranting anti-inflammatory drugs and did not take this into account in the subsequent analyses. Sabioncello and colleagues found that women who were displaced from their home after war displayed several signs of peripheral immune activation compared to controls, although psychiatric symptoms were recorded only by Self Report and no formal PTSD diagnosis was made (Sabioncello et al, 2000).…”
Section: General Findingsmentioning
confidence: 99%
“…Tucker et al (2004) found higher levels of IL-1 and lower levels of IL2-receptor in PTSD subjects compared to traumatized controls, although a potential limitation of this study was that they included several PTSD subjects with inflammatory conditions warranting anti-inflammatory drugs and did not take this into account in the subsequent analyses. Sabioncello and colleagues found that women who were displaced from their home after war displayed several signs of peripheral immune activation compared to controls, although psychiatric symptoms were recorded only by Self Report and no formal PTSD diagnosis was made (Sabioncello et al, 2000).…”
Section: General Findingsmentioning
confidence: 99%
“…Indeed, delayed-type hypersensitivity (DTH) was found enhanced in women with PTSD due to childhood sexual or physical abuse [8] . ) cell subpopulations in women with PTSD due to war displacement have been reported [9] . Lymphocytes expressing the late (CD71 + ) but not the early (CD25 + ) activation marker were also elevated in displaced women.…”
Section: Increased Cell-mediated Immunity and Activation Phenotypementioning
confidence: 99%
“…Increased counts of activated T (CD2+HLA-DR+), NK (CD16+CD71+) and B (CD20+CD23+) cell subpopulations in women with PTSD due to war displacement have also been reported [36]. Lymphocytes expressing the late (CD71+) but not the early (CD25+) activation marker were also elevated in displaced women.…”
Section: Immune Imbalance: Evidence For Low-grade Inflammationmentioning
confidence: 97%
“…Several alterations in the number, activity and preferential cellular expansions have been reported. In general, PTSD is associated with enhanced cellular immune responses [33], a higher number of total lymphocytes [34], an increased number and activity of NK cells [35], and activated T lymphocytes [35,36]. Also, an altered balance between Th1/Th2 immune responses seems to be shifted towards the Th1 profile.…”
Section: Immune Imbalance: Evidence For Low-grade Inflammationmentioning
confidence: 99%